2021
DOI: 10.1016/j.radonc.2021.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nodal failure after radiochemotherapy and image guided brachytherapy in locally advanced cervical cancer: An EMBRACE analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Extending pelvic radiotherapy fields to the PALN region in patients with no suspicious PALNs has not been studied in a modern randomized trial. Such 'prophylactic' PALN irradiation resulted in improved progression-free survival in some cohort studies [38,39], but not in others [40,41], and its role is therefore not clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Extending pelvic radiotherapy fields to the PALN region in patients with no suspicious PALNs has not been studied in a modern randomized trial. Such 'prophylactic' PALN irradiation resulted in improved progression-free survival in some cohort studies [38,39], but not in others [40,41], and its role is therefore not clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic para-aortic radiotherapy can effectively mitigate the risk of para-aortic nodal failure,3–8 and we found that anatomy-based definition of the para-aortic nodal region may further optimize treatment outcomes of prophylactic para-aortic radiotherapy. However, distant failures were the main patterns of failure in our study, which is in line with a previous large study 23.…”
Section: Discussionmentioning
confidence: 70%
“…External beam radiotherapy was delivered by intensity-modulated radiotherapy using 6 or 10 MV photons in all patients. At our institutions, prophylactic extended-field radiotherapy was administered to patients with common iliac or multiple pelvic lymph nodes (≥3 pelvic lymph nodes), bulky tumors (size ≥5 cm), or FIGO stage IIIA–B disease 2–6. Prophylactic extended-field intensity-modulated radiotherapy was performed at 45 Gy in 25 fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant opportunity to improve normal tissue toxicity with proton therapy in gynecologic malignancies is the use of proton therapy to treat para-aortic disease in extended-field radiotherapy. In cervical cancer, for example, there is renewed attention to treatment of the para-aortic nodes, given that PET/CT scanning may potentially not detect a quarter of para-aortic nodes involved; additionally, involvement of three or more pelvic lymph nodes or the common iliac nodes increases risk of para-aortic node involvement 39. Treatment of these nodal regions is challenging given significant amounts of bowel, kidney, spine, and other exposed organs.…”
Section: Para-aortic Nodal Radiationmentioning
confidence: 99%